The Long-Term Ecological Research community metadata standardisation project: a progress report. (11th August 2009) - San Gil, Inigo; Baker, Karen; Campbell, John; Denny, Ellen G.; Vanderbilt, Kristin; Riordan, Brian; Koskela, Rebecca; Downing, Jason; Grabner, Sabine; Melendez, Eda; Walsh, Jonathan; Kortz, Mason; et al.
We describe the process by which the Long-Term Ecological Research (LTER) Network standardised their metadata through the adoption of the Ecological Metadata Language (EML). We describe the strategies developed to improve motivation and to complement the information technology resources available at the LTER sites. EML implementation is presented as a mapping process that was accomplished per site in stages, with metadata quality ranging from 'discovery level' to rich-content level over time. As of publication, over 6000 rich-content standardised records have been published using EML, potentially enabling the goal of machine-mediated, metadata-driven data synthesis.